Structurally simple inhibitors of lanosterol 14alpha-demethylase are efficacious in a rodent model of acute Chagas disease. - Suryadevara, P; Olepu, S; Lockman, J; Ohkanda, J; Karimi, M; Verlinde, C; Kraus, J; Schoepe, J; Van Voorhis, W; Hamilton, A; Buckner, F; Gelb, M (2009)
We report structure-activity studies of a large number of dialkyl imidazoles as inhibitors of Trypanosoma cruzi lanosterol-14alpha-demethylase (L14DM). The compounds have a simple structure compared to posaconazole, another L14DM inhibitor that is an anti-Chagas drug candidate. Several compounds display potency for killing T. cruzi amastigotes in vitro with values of EC(50) in the 0.4-10 nM range. Two compounds were selected for efficacy studies in a mouse model of acute Chagas disease. At oral doses of 20-50 mg/kg given after establishment of parasite infection, the compounds reduced parasitemia in the blood to undetectable levels, and analysis of remaining parasites by PCR revealed a lack of parasites in the majority of animals. These dialkyl imidazoles are substantially less expensive to produce than posaconazole and are appropriate for further development toward an anti-Chagas disease clinical candidate.